Verso il restauro Temi, tesi, progetti per la conservazione - De Vita, Maurizio (Strumenti per la didattica e la ricerca, 2012)
The book brings together critical considerations and experiences linked to the work of the author, lecturer in restoration at the Florence University Faculty of Architecture, as supervisor of degree theses on restoration. The reflections concern teaching Restoration as a subject, the conditions within which the knowledge and culture of restoration can ripen within our universities and the most recent problems encountered by both the discipline and restoration projects. In the first part of the publication, these aspects are set out in broad and more precisely conceptual and methodological terms in chapters and themed paragraphs which also act as a guide to drawing up degree theses on restoration, as well as a contributing to the didactics and efficiency of the specific discipline. This is followed by a selection of degree theses on restoration discussed in recent years which show the route from the principles, general problems and intervention criteria for every case study to drawing up a project. They are projects that deal with analysis methods and techniques, surveys, specialist restorations, regeneration, and the relationship between old and new. In short, the projects are what gave the final stage in the university education meaning and substance, also in order to acquire fundamental keys to restoration culture and activities in the world after university.